Effects of ultraviolet solar radiation on the properties of particulate-filled epoxy based polymer coating - Khotbehsara, Mojdeh Mehrinejad; Manalo, Allan; Aravinthan, Thiru; Turner, Joanna; Ferdous, Wahid; Hota, Gangarao (Polymer degradation and stability, 2020)
•Properties and microstructure of particulate-filled epoxy-based coating under UV exposure.•Particulate fillers make epoxy resin with a dense microstructure after UV exposure.•Exposure to a xenon arc lamp at a temperature of 60 °C for 2000 h is equivalent to 5 years of UV exposure in the field.•Less thickness of coating is required if particulate fillers are added to the epoxy resin. Exposure to solar ultraviolet (UV) radiation causes photochemical damage near the exposed surface, which results in the degradation of composite reinforcing elements. To minimise the UV degradation, epoxy polymers are being applied as protective coatings to composite materials to retain properties during their design service life. In this study, the effects of UV exposure on the physical, mechanical, and thermo-mechanical properties, including the microstructure particulate-filled epoxy-based polymer coating, were investigated. The polymer coating contains up to 60% by volume of hydrated alumina powder fire retardant (FR) and fillers such as an industrial waste like fly ash (FA) and is exposed to simulated UV conditions either 1000 h or 2000 h. Physical observations showed yellowing at the surface of neat epoxy coating after UV exposure but the presence of particulate FR and FA fillers minimised fading and weight loss. Similarly, no reduction in the flexural strength was observed for polymer coating containing at least 40% fillers, indicating that the FR and FA retained the structural performance of the coating. SEM observation revealed formation of microcracks in the surface of the neat epoxy resin but a dense microstructure in particulate filled epoxy resin after exposure to UV radiation. FTIR analyses indicated that photo-degradation due to UV radiation was limited only on the thin surface of the coating. From the results of this study, a coating thickness of at least 11 mm is required for epoxy based polymer coating with 60% by volume fillers, which is 5 times thinner than neat epoxy resin, to provide 100 years of UV resistance.